PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN TUNJANGAN TERHADAP EFEKTIVITAS KERJA KARYAWAN MELALUI SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING (STUDY KASUS PT FAJAR INSAN NUSANTARA DENPASAR-BALI) - Wahyuni, Wahyuni; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze and test the influence of Competence, Work Experience, and Allowances on the Work Effectiveness of employees at PT. Fajar Insan Nusantara Bali through Work Spirit. The population in this study consists of employees of PT. Fajar Insan Nusantara Bali. The sampling technique used is quota sampling. Data analysis and hypothesis testing in this research were conducted using the Structural Equation Model – Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that competence has a positive but not significant effect on work spirit, work experience has a negative and significant effect on work spirit, and allowances have a negative and significant effect on work spirit. Competence has a significant negative effect on work effectiveness, work experience has a positive but not significant effect on work effectiveness, and allowances have a positive but not significant effect on work effectiveness. Work spirit has a positive and significant effect on work effectiveness. The indirect influence of competence on work effectiveness through work spirit is positive but not significant, while work experience has a negative and significant effect on work effectiveness through work spirit, and allowances have a negative and significant effect on work effectiveness through work spirit.